Infestation and histopathology of Clinostomum sp. (Digenea: Clinostomidae) in snakeskin fish (Trichopodus pectoralis Regan, 1910) in Tempe Lake, South Sulawesi, Indonesia - IKA IKA; HILAL ANSHARY; SRIWULAN SRIWULAN (Society for Indonesian Biodiversity, 2024)
Abstract. Ika, Anshary H, Sriwulan. 2024. Infestation and histopathology of Clinostomum sp. (Digenea: Clinostomidae) in snakeskin fish (Trichopodus pectoralis Regan, 1910) in Tempe Lake, South Sulawesi, Indonesia. Biodiversitas 25: 3263-3272. Fish diseases caused by parasites seriously threaten the aquaculture industry and wild fish populations in natural water. This research aims to identify and characterize the digenetic trematode Clinostomum sp. based on morphology and molecular characteristics and analyze the level of infestation and histopathological changes of the endoparasite infestation in snakeskin fish across three lakes (Tempe Lake, Lampulung and Latamperu Lakes) in South Sulawesi, Indonesia. A total of 300 snakeskin fish were collected from a survey conducted from July 2023 to January 2024 for parasite examination. The morphological identification of parasites, a meticulous process, was carried out to distinguish digenean species that infect snakeskin fish populations, ensuring the accuracy of our findings. The results showed that Clinostomum sp., was found infesting snakeskin fish across all three lakes within Wajo District, and the identity of the parasite was further confirmed with Polymerase Chain Reaction (PCR) and sequencing on the Internal Transcribed Spacer (ITS)-5.8S region. The prevalence and mean intensity of the parasite infestation varied among the three locations surveyed, though they are not different statistically; Lampulung Lake showed a prevalence of 34%, Latamperu Lake at 28%, and Tempe Lake at 21%. The mean intensity of infestation in Lampulung Lake at 10±10.70, Latamperu Lake at 09±12.82, and Tempe Lake at 06±6.22. Histopathological analysis showed changes within the intestinal tissues of snakeskin fish associated with the infestation of Clinostomum sp., including goblet cells, hemorrhage, and cellular infiltration. This study demonstrated a consistent presence of Clinostomum sp. across all lakes, with relatively high prevalence and mean intensity of infestation. The histopathological analysis showed mild tissue alterations in infested fish. However, the high prevalence of infestation of the zoonotic digenetic trematode raises concerns about the public health impacts for local communities who consume raw or undercooked fish.